Salivary glands in Svalbard reindeer (Rangifer tarandus platyrhynchus) and in Norwegian reindeer (Rangifer tarandus tarandus) - Mathiesen, Svein D.; Rædergård, V. B.; Vader, M. A.; Haga, Ø. E.; Norberg, H. J.; Sørmoe, W.; Tyler, N. J. C. (Rangifer, 1999)
The aim of this investigation was to compare the size of salivaty glands in Svalbard reindeer {Rangifer tarandus platyrhynchus) and in Norwegian reindeer (Rangifer t. tarandus) in relation to feeding strategy, season and reproductive status. The mean body mass (BM, standard deviation j) in adult non-lactating female Svalbard reindeer was 72.0, s = 4.2, kg (n = 8) in September and 46.7, s = 7.1, kg (« = 4) in April. The mean BM of adult non-lactating Norwegian reindeer was 67.5, s = 7.7, kg (» = 8) in September and 59.2, s = 9.6, kg (n = 9) in March. In non-lactating female Svalbard reindeer the mean combined mass of parotid glands was 82.7, s = 4.5, g in September and 58.8, s = 8.7, g in April (P < 0.05). In the Norwegian reindeer the mean combined mass of the parotid glands was 95.2, s = 14.4, g in Septembet and 68.1, s = 9.5, g in Match (P < 0.05). We wete not able to find any sub-species differences in the size of the salivaty glands which could be related to phenotypic difference in feeding strategy. Both sub-species had parotid glands sizes similar to that of intermediate ruminant types, ranging from 0.11-0.14% of BM. The larger absolute size of salivaty glands in summer compared to winter reflects the importance of high rates of production of saliva when the dry matter intake and microbial fermentation is high.